Implementation of Discovery Flipped Learning as an Alternative Approach to Enhance Critical Thinking Skills - Dadi Rosadi; Mustaji mustaji; Andi Mariono; Khusnul Khotimah (Akademika, 2024)
This study aims to analyze the effect of Discovery Flipped Learning on the critical thinking skills of grade VII students on the material of Quantity and Measurement at Indonesian School Kuala Lumpur and to compare the effectiveness between Discovery Learning and Discovery Flipped Learning in improving students' critical thinking skills. This is a quasi-experimental study with a non-equivalent control group design. The study subjects were all grade VII students of Junior High School at the Indonesian School in Kuala Lumpur, totaling 23 students for each experimental and control class. Sampling was carried out using a purposive sampling technique, where class VII A was the experimental class and class VII B was the control class. We tested the critical thinking skills of the control class and the experimental class using a test instrument in the form of descriptive questions. The results of the analysis showed that H0 was rejected and H1 was accepted, which showed a significant effect of Discovery Flipped Learning on students' critical thinking skills, as well as a substantial difference compared to Discovery Learning. Discovery Flipped Learning is recommended as an effective alternative to be implemented at all grade levels at Indonesian School Kuala Lumpur.